Individual variability of human cerebellar arteries and their perfusion territories - Kalinichenko, M.O.; Stepanenko, O.Yu. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Three paired arteries provide the blood supply of the cerebellum: the superior cerebellar artery, anterior inferior cerebellar artery, and posterior inferior cerebellar artery. The origin of these arteries, the extent of their development and their duplication may serve as factors influencing variations in the vascular supply territories. The aim of this study was to determine the characteristics of individual variability of the human cerebellar arteries and their perfusion territory. Methods. The study was conducted on 100 samples. Each sample included cerebellum and an adjacent brainstem. They were obtained from adult human cadavers (67 male and 33 female) who died of causes unrelated to brain pathology at the age between 20 and 92. To analyze the variability of perfusion territories of the cerebellar arteries, a method involving sectorial division of the superior and inferior surfaces of the cerebellum was proposed. Results and conclusion. In 95 samples, the SCA arose from the basilar artery on both sides as a single vessel. In two samples, it arose as a duplicate trunk from the basilar artery bilaterally. We also found unilateral duplication of the left SCA in three samples. The AICA arose from the lower third of the basilar artery in 69 samples on the right and in 77 on the left; from the middle third in 11 on the right and 11 on the left. It was presented as a common trunk with the PICA in 18 samples on the right and 10 on the left. The AICA was found duplicated in one sample bilaterally. In two samples it was absent on one side. The PICA most often arose from the vertebral artery (82 samples), rarely as a common trunk with AICA. It was duplicated in two samples on the left and absent in four samples on the right and four on the left. In cases of duplication of the PICA, its perfusion territory expands towards the central sectors of the inferior surface of the cerebellum. In the absence of the AICA, the PICA enlarges its perfusion territory, replacing it, and vice versa. Occasionally, the absent or poorly developed PICA is replaced by a PICA from the opposite hemisphere. There were not any cases of simultaneous absence of both AICA and PICA on one side. The probability of the extension of branches of the AICA onto specific sectors of the inferior surface of the cerebellum decreases from anterior to posterior and from the sides towards the center, while for the PICA there is an opposite trend. Additionally, this study describes three variations of the course of the arteries when both AICA and PICA originate as a common trunk from the basilar artery.